The 5'-flanking region of the mouse muscle nicotinic acetylcholine receptor beta subunit gene promotes expression in cultured muscle cells and is activated by MRF4, myogenin and myoD. - Prody, C A (1992)
The expression of the nicotinic acetylcholine receptor (AChR) in vertebrate striated muscle is regulated both during development by nerve-evoked muscle activity and by local factors released or associated with the nerve ending. The expression pattern of AChR is achieved by coordinate regulation of four embryonic subunit mRNAs, alpha, beta, gamma and delta. We have taken the approach of identifying the similarities and differences among cis-acting regulatory elements of AChR genes to gain a better understanding of these mechanisms. Thus, to begin to define DNA sequences necessary for the transcriptional regulation of the mouse beta AChR gene, we have analyzed its 5'-flanking region. Primer extension and RNAase protection analyses showed that transcription initiates at one major and two minor sites, all of which are close to the translational initiation site. Using plasmids in which segments of the 5'-flanking region were linked to the bacterial chloramphenicol acetyltransferase (CAT) gene, we have demonstrated that 150 bp of the 5'-flanking region is active in C2 myotubes but not C2 myoblasts or NIH3T3 fibroblasts. This region contains a putative binding site for myoD, and when linked to CAT was transactivated by the muscle regulatory factors myoD, myogenin, and MRF4. Thus, a 150 bp sequence of the beta-subunit gene contains information necessary for developmental specificity and responsiveness to myogenic factors.